Benzene Exposure Leads to Lipodystrophy and Alters Endocrine Activity In Vivo and In Vitro - Cui, Ying; Mo, Ziying; Ji, Penglei; Zhong, Jingyi; Li, Zongxin; Li, Daochuan; Qin, Lina; Liao, Qilong; He, Zhini; Guo, Wei; Chen, Liping; Wang, Qing; et al. (Frontiers in Endocrinology, 2022)
Benzene is a ubiquitous pollutant and mainly accumulates in adipose tissue which has important roles in metabolic diseases. The latest studies reported that benzene exposure was associated with many metabolic disorders, while the effect of benzene exposure on adipose tissue remains unclear. We sought to investigate the effect using in vivo and in vitro experiments. Male adult C57BL/6J mice were exposed to benzene at 0, 1, 10 and 100 mg/kg body weight by intragastric gavage for 4 weeks. Mature adipocytes from 3T3-L1 cells were exposed to hydroquinone (HQ) at 0, 1, 5 and 25 μM for 24 hours. Besides the routine hematotoxicity, animal experiments also displayed significant body fat content decrease from 1 mg/kg. Interestingly, the circulating non-esterified fatty acid (NEFA) level increased from the lowest dose (ptrend < 0.05). Subsequent analysis indicated that body fat content decrease may be due to atrophy of white adipose tissue (WAT) upon benzene exposure. The average adipocyte area of WAT decreased significantly even from 1 mg/kg with no significant changes in total number of adipocytes. The percentages of small and large adipocytes in WAT began to significantly increase or decrease from 1 mg/kg (all p < 0.05), respectively. Critical genes involved in lipogenesis and lipolysis were dysregulated, which may account for the disruption of lipid homeostasis. The endocrine function of WAT was also disordered, manifested as significant decrease in adipokine levels, especially the leptin. In vitro cell experiments displayed similar findings in decreased fat content, dysregulated critical lipid metabolism genes, and disturbed endocrine function of adipocytes after HQ treatment. Pearson correlation analysis showed positive correlations between white blood cell (WBC) count with WAT fat content and plasma leptin level (r =0.330, 0.344, both p < 0.05). This study shed light on the novel aspect that benzene exposure could induce lipodystrophy and disturb endocrine function of WAT, and the altered physiology of WAT might in turn affect benzene-induced hematotoxicity and metabolic disorders. The study provided new insight into understanding benzene-induced toxicity and the relationship between benzene and adipose tissue.